2015
DOI: 10.1016/j.siny.2014.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Movement disorders due to bilirubin toxicity

Abstract: Summary Advances in the care of neonatal hyperbilirubinemia have decreased the incidence of kernicterus. However, neonatal exposure to high levels of bilirubin continues to cause severe motor symptoms and cerebral palsy (CP). Exposure to moderate levels of unconjugated bilirubin may also cause damage to the developing central nervous system, specifically the basal ganglia and cerebellum. Brain lesions identified using magnetic resonance imaging following extreme hyperbilirubinemia have been linked to dyskineti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
47
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 34 publications
0
47
0
1
Order By: Relevance
“…Our study showed that the changes of MK between NBE and control newborns were greater in the globus pallidus than in the putamen and thalamus, which may illustrate that the greatest internal environment change of globus pallidus, probably due to its location in the circuit of the basal ganglia. The internal globus pallidus contains output neurons of the basal ganglia, which project through the motor thalamus and back to the motor cortex (2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study showed that the changes of MK between NBE and control newborns were greater in the globus pallidus than in the putamen and thalamus, which may illustrate that the greatest internal environment change of globus pallidus, probably due to its location in the circuit of the basal ganglia. The internal globus pallidus contains output neurons of the basal ganglia, which project through the motor thalamus and back to the motor cortex (2).…”
Section: Discussionmentioning
confidence: 99%
“…Neonatal bilirubin encephalopathy (NBE) is a relatively rare neurological syndrome caused by the deposition of unconjugated bilirubin in brain cells; the damage inflicted on the brain by bilirubin is not always reversible (1,2). The condition has recently become more prevalent because of the relaxed standards for rapid and aggressive intervention, early hospital discharge, and increased practice of breastfeeding (2,3). The mechanisms of NBE neurotoxicity are unclear but generally considered to be related to the deposition of unconjugated bilirubin in the central nervous system (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Total bilirubin is composed of conjugated and unconjugated bilirubin [8]. Unconjugated bilirubin is a potent neurotoxin, which, by crossing the blood-brain barrier, may injure neural cells.…”
Section: Introductionmentioning
confidence: 99%
“…However, neonatal exposure to high levels of bilirubin continues to cause CP. New categories of bilirubin-induced neurological dysfunction, either independent or characterised by subtle bilirubin encephalopathy following moderate hyperbilirubinemia, have been implicated in long-term motor function [13].…”
Section: Introductionmentioning
confidence: 99%
“….053 AR* -attributable risk, the effect of a risk factor on the exposed group % (10) 53 (21) 48 (19) 52 2118 772 2932 (13) 13 516 (6) 269 (78) 54 (16) 57 (16) 35 (10) 33 1014 (4) 92 (27) 31 911 35 (1) . Flowchart showing inclusion in the study population…”
mentioning
confidence: 99%